A Safety and Efficacy Study of a Synthetic Biolubricant in an Equine Model of Post-Traumatic Osteoarthritis - Lauren K. Luedke; Kathryn A. Seabaugh; Benjamin G. Cooper; Brian D. Snyder; Markus A. Wimmer; C. Wayne McIlwraith; Myra F. Barrett; Christopher E. Kawcak; Mark W. Grinstaff; Laurie R. Goodrich (Animals)
Post-traumatic osteoarthritis (PTOA) is a common cause of lameness in the horse. There is no cure, therefore treatments are aimed at reducing pain and improving the joint environment by modifying inflammatory pathways or by viscosupplementation. Here, we report the safety and efficacy of the biolubricant (poly(2-methacryloyloxyethyl phosphorylcholine; pMPC) to mitigate the physical, gross, histological, and biochemical effects of arthritis. We created an osteochondral fragment in the middle carpal joint of one limb in 16 horses to induce PTOA; the contralateral limb served as a sham-operated joint. Two weeks postoperative, half (n = 8) of the horses received a single injection of pMPC in the PTOA joint, while the other half received saline. All sham-operated joints (n = 16) received saline. We conducted clinical evaluations weekly while synovial fluid biomarkers were measured biweekly during the 70-day study period. Subsequently, we performed postmortem gross and histologic analyses. Horses in which PTOA joints were treated with pMPC exhibited mild increases in clinical data, including lameness, effusion, and flexion scores. Similarly, synovial cell count, total protein, and prostaglandin E2 values were higher for pMPC-treated joints. Radiographic changes included significantly higher osteophyte scores in pMPC-treated joints at the terminal timepoint. The biolubricant may demonstrate some chondroprotective effects with lower total erosion scores and higher cartilage glycosaminoglycan content. In summary, when pMPC is administered to PTOA joints, the biolubricant induces a mild inflammatory response but may offer some chondroprotective effects in horses.